Evolutionary characteristics, regional differences and spatial effects of coupled coordination of rural revitalization, new-type urbanization and ecological environment in China - Zhang, Ruijuan; Bao, Qingfeng (Frontiers in Environmental Science, 2024)
Rural revitalization (R), new-type urbanization (U) and the ecological environment (E) are a unity of complementary advantages and mutual promotion and coexistence, the coupling and coordination of the three is the key to realizing the Chinese modernization and the harmonious coexistence of human beings and nature. Based on China’s provincial panel data from 2011 to 2022, this paper constructed a comprehensive evaluation index for the R-U-E system, using the entropy method, coupled coordination model, Dagum’s Gini coefficient, kernel density estimation, spatial correlation analysis, and spatial Durbin model to explore the level of comprehensive development, spatial-temporal evolutionary characteristics of coupled coordination, regional differences and spatial effects of the three systems. The following results were observed: (1) The comprehensive index of rural revitalizationand new-type urbanization exhibits a growing trend and significant regional differences, with East China outperforming other regions, but the average value of below 0.5 needs to be further improved. The ecological environment index exhibits a smoother growth trend, higher in South China than in other regions. (2) The level of R-U-E coupling coordination has increased year on year, from barely coordinated to primary coordination. (3) The spatial imbalance in coupling coordination has improved both nationally and in the seven regions, with the largest intra-regional differences in South China and the smallest intra-regional differences in Central China. The differences between the Northeast and Central China regions exhibit a widening trend, while the differences between all other regions exhibit a decreasing trend. Interregional variations are the main factor affecting overall variance, but their impact on the overall variance is gradually diminishing. (4) The level of coupling coordination has obvious spatial correlation, and the “high-high” and “low-low” cluster aggregation characteristics was evident. (5) Government behavior and the levels of economic growth, human capital, and digitization significantly contribute to the coupled and coordinated development of the region and, at the same time, have a significant spatial spillover effect on neighboring provinces; the degree of openness to the outside world contributed to the coordinated development of the region, while it had an inhibitory effect on the neighboring provinces; and the drive to innovate has only a certain contributing effect on the neighboring regions. Targeted policy measures in response to this paper’s empirical findings may provide policymakers with a reference point for achieving regional sustainable development goals.